MENUMBUHKAN SIKAP NASIONALISME DAN BELA NEGARA MAHASISWA MELALUI PENDIDIKAN KEWARGANEGARAAN DI PERGURUAN TINGGI - Riza Hasan (Jurnal Tunas Pendidikan, 2022)
ABSTRACT This study aims to find out how efforts to grow students' nationalism and state defense attitudes through civic education in universities. This research was conducted at the West Aceh State Community Academy. This research is a qualitative research, data collection using interviews, observation, documentation and focus group discussion. Data analysis through data reduction, data presentation, and drawing conclusions. The results of this study stated that students' understanding of nationalism and state defense was in accordance with what was expected. Efforts to foster an attitude of nationalism and state defense to students are carried out using an experience-based learning model and an interactive model, in order to stimulate students' willingness to think critically with the aim of sharpening students' abilities in understanding what material is conveyed and can be directly exemplified by experience and daily habits. Characteristics of the nationalist attitude of AKN Aceh Barat students, namely loving the State of Indonesia, caring and willing to sacrifice. While the characteristics of AKN students related to the attitude of defending the country are knowing their obligations as citizens, having good morals and accompanied by skills or skills according to their field of expertise. Keywords: Attitude, Nationalism, State Defense, Citizenship Education